PERCEPTION OF HEALTH PROFESSIONALS TOWARDS THE SCOPE OF FAMILY MEDICINE IN THE HEALTHCARE SYSTEM OF PAKISTAN - Khan, Abdul Jalil; Ahmad, Sajad; Aziz, Mohammed (Journal of Ayub Medical College Abbottabad, 2018)
Background: Background: Primary health care is the backbone of comprehensive healthcare systems, and family physicians complement horizontal health coverage. In the developed world family medicine is integral to new doctors' training but, in the developing world, there are hurdles, e.g., poorly targeted financing, lack of skills and resources, and little health professionals' interest in the specialty. Method: This study determined perceptions of undergraduate and postgraduate medical trainees and healthcare professionals in Pakistan about family medicine. Participants' perceptions were examined via a self-administered pre-structured questionnaire about family medicine in developing countries before and after a targeted seminar. Epi Info software (v.7) was used for statistical analysis. The p-value <0.05 was considered statistically significant. Results: 108 questionnaires were returned post-seminar demonstrating raised participant awareness of family medicine, with the majority (postgraduate 90.00% and undergraduate 90.91%) believing that health departments should create family medicine specialist posts to encourage students and post-graduate trainees. Similarly, 89.77% undergraduates and 95.00% postgraduates believed that comprehensive family medicine in primary health could be a solution to improve health care in Pakistan. Of note, when asked pre-seminar "do you feel you would consider family medicine as career speciality?", 42% undergraduates replied yes; when asked the same question post-seminar 63% of undergraduates and 90% of postgraduates replied yes. Conclusion: Introducing family medicine as a subject in medical colleges will create awareness and interest towards this speciality; until then, awareness lectures and seminars by trained family physicians will help bridge the gap towards encouraging students about its benefits. Keywords: General Practice; Physician; Family